Implementation of Project-Based Learning Strategies in Improving the Quality of Proposals and Student Learning Outcomes to Accelerate Thesis Completion - Suprapto, Edy; Kuswara, Ketut Mahendra; Harijono (Migration Letters, 2023)
The purpose of this research is to apply and develop project-based learning strategies in the Educational Research Methods Course to improve the quality of research proposals, so as to accelerate the completion of thesis assignments in the Mechanical Engineering Education Study Program at Nusa Cendana University. Conditions in the field show that the completion of the thesis is still quite long on average 12 months or more, thus prolonging the study period of students. This research is quasi-experimental research with a Nonequivalent Control Group Design, which was conducted on students of the mechanical engineering education study program at Nusa Cendana University who programmed the educational research methods course. Consisting of an experimental class of 30 students who received project-based learning strategy treatment and a control class of 30 students with conventional learning strategy treatment. The analysis requirement test was conducted with normality and homogeneity tests. Data analysis techniques using descriptive analysis and t test. The results showed that: (1) the application of project-based learning strategies is superior in increasing the number of proposal products with good quality (22 proposals) compared to the application of conventional learning strategies (11 proposals); (2) the application of project-based learning strategies is able to improve learning outcomes (mean 80.233) compared to the application of conventional strategies (mean 74.367); (3) Another advantage of applying project-based learning strategies is that it can improve students’ abilities in problem solving, collaborative teamwork, peer learning, and high self-confidence, as well as being responsible for timely proposal assignments which become the final product of the educational research methods course.